Saturnine Vision and the Question of Difference: Reflections on Walter Benjamin's Theory of Language - Rodolphe Gasché (Studies in 20th & 21st Century Literature, 1986)
Walter Benjamin's writings do not owe their intelligibility to their indebtedness to one or more specific brands of philosophical thought, but to Benjamin's primary concern with the most elementary distinctions of philosophy itself. Chief among these distinctions is that of philosophical thought itself, or the difference it makes with respect to the realms of nature, myth, or the appearances. By focusing on the notions of "communicability" and "translatability," philosophical difference, for Benjamin, shall be shown to rest on structures within the language of man and art that aim at breaking through language's mythical interconnectedness, its weblike quality, its textuality, toward the absolute Other of divine language. Yet, the fundamental philosophical law not to mix genres or realms, as well as the transcending power of philosophical difference, because it remains caught in what it seeks to transgress, are dependent, as far as their success is concerned, on the ultimate justification by the (theological) difference of the absolute Other of divine language. It is, however, not in the power of philosophy to secure all by itself this necessary legitimation.
Keywords: Walter Benjamin; philosophical thought; philosophy; nature; myth; appearances; communicability; translatability; language; structures; art; man; theological; devine language; Other